Episodic idiopathic systemic capillary leak syndrome in a girl. Issue 4 (5th August 2013) - Milani, Gregorio Paolo; Dellepiane, Rosa Maria; Castellazzi, Massimo Luca; Mazzoni, Marta Benedetta Maria; Bianchetti, Mario Giovanni; Fossali, Emilio Filippo
Abstract: Episodic idiopathic systemic capillary leak syndrome is a rare disorder that presents with attacks of circulatory shock due to plasma leakage into the extravascular space. Reported here is the case of a girl who had recurrent circulatory shock. The diagnosis of episodic idiopathic systemic capillary leak syndrome was made following the fourth episode. The course was favorable following acute i.v. cristalloids and methylprednisolone.